Perempuan Pekerja Migran: Kajian Perlindungan Personal Human Security Tenaga Kerja Indonesia - Vidi Milathul Faudzan (Jurnal Sentris, 2019)
In 2016, the number of Indonesian migrant workers (TKI) are counted 3,510,000. 4,860 of them were reported complaining of violence, and there were 217 TKI reported dead in the same year. The facts and data that have been submitted, show that female Indonesian migrant workers who work in the informal sector are very vulnerable to acts of threats and other hazards. These violence and threats clearly endanger their human security. Departing from this, the author will be researching on the factors why the community chose to become TKI and how to implement human security for female migrant workers currently carried out by the Government of Indonesia. The method used in this study is descriptive qualitative with data collection techniques through interviews and literature studies. Based on the results of research conducted in the UU No. 18 Tahun 2017, it has guaranteed the safety of migrant workers, but not related to specific gender.